When are organizations punished for organizational misconduct? A review and research agenda. (2021) - McDonnell, Mary-Hunter; Nurmohamed, Samir
Abstract: Scholars have highlighted the use of punishment as a tool to defend laws and norms, deter deviance, and restore justice in the aftermath of organizational misconduct. However, current theory and research primarily draw on a micro-oriented lens to understand how punishment occurs in response to deviant actors within organizations, neglecting macro-oriented questions of whether and how organizations are punished for their misconduct. We review sociological and macro-organizational work that suggests punitive severity can vary with three key attributes of the organization: status, reputation, and embedded ties. We then develop a mezzo-lens framework motivated at the intersection of micro- and macro-perspectives on organizational misconduct to shed light on opportunities for theoretical expansion by crossing levels of analysis.